Portuguese cultural standards from Colombian perspective - Flórez Sanjuán, Sergio Andrés (2012)
Working and doing business with people from other cultures and countries has become the most common situation in the globalized world of today. The way we deal with perceptions, judgments, ways of thinking and actions are some of the most important factors for good performance or for successfully achieving an objective either individually or within a team, hence identifying cultural differences is crucial in helping us avoid unnecessary misinterpretations. The objective of this work is to look for cultural differences with a qualitative approach and identify cultural standards of Portuguese people from the perspective of Colombian people working in Portugal. For this purpose the author will interview Colombian people working in Portugal in order to gather experiences and analyze multiple situations to find common points that can lead us to identify Portuguese cultural standards and eventually make a comparison with Hosftede’s findings about the countries studied in this research.